A double‐quadrature radiofrequency coil design for proton‐decoupled carbon‐13 magnetic resonance spectroscopy in humans at 7T. Issue 2 (3rd March 2014) - Roig, Eulalia Serés; Magill, Arthur W.; Donati, Guillaume; Meyerspeer, Martin; Xin, Lijing; Ipek, Ozlem; Gruetter, Rolf
<x xml:space="preserve">Abstract</x> Purpose Carbon‐13 magnetic resonance spectroscopy (13C‐MRS) is challenging because of the inherent low sensitivity of 13C detection and the need for radiofrequency transmission at the 1H frequency while receiving the 13C signal, the latter requiring electrical decoupling of the 13C and 1H radiofrequency channels. In this study, we added traps to the 13C coil to construct a quadrature‐13C/quadrature‐1H surface coil, with sufficient isolation between channels to allow simultaneous operation at both frequencies without compromise in coil performance. Methods Isolation between channels was evaluated on the bench by measuring all coupling parameters. The quadrature mode of the quadrature‐13C coil was assessed using in vitro 23Na gradient echo images. The signal‐to‐noise ratio (SNR) was measured on the glycogen and glucose resonances by 13C‐MRS in vitro, compared with that obtained with a linear‐13C/quadrature‐1H coil, and validated by 13C‐MRS in vivo in the human calf at 7T. Results Isolation between channels was better than −30 dB. The 23Na gradient echo images indicate a region where the field is strongly circularly polarized. The quadrature coil provided an SNR enhancement over a linear coil of 1.4, in vitro and in vivo. Conclusion It is feasible to construct a double‐quadrature 13C‐1H surface coil for proton decoupled sensitivity enhanced 13C‐NMR spectroscopy in humans at 7T. Magn Reson Med 73:894–900, 2015. © 2014 Wiley Periodicals, Inc.